Evaluation of the operational efficiency of GH Zadar department using the DEA method - Jukić, Zdenko (Oeconomica Jadertina, 2026)
This paper analyzes the efficiency of hospital departments at Zadar General Hospital using Data Envelopment Analysis (DEA). The focus is on optimizing input and output activities of these departments to enhance their operational efficiency. The methodology involves constructing a linear frontier function based on collected input and output departmental data. The analysis employs the following parameters - inputs: number of hospital beds (P) and number of employed physicians (L), and outputs: number of discharged patients (BOB) and number of performed examinations (BOP). The CCR model is utilized to analyze hospital efficiency, demonstrating how departments could reduce their inputs while maintaining the same output levels, or alternatively, increase their outputs while maintaining current input levels. Data Envelopment Analysis is employed to measure the relative efficiency of departments compared to their peers and to identify specific factors that explain their efficiency. Results indicate significant variability in departmental efficiency, suggesting opportunities for improvement. Key findings emphasize the need for continuous evaluation and enhancement of departmental operational efficiency, coupled with the implementation of targeted training programs and technological investments. Specific strategies are proposed, including consolidation, specialization, and improved resource management to achieve optimal efficiency. In conclusion, this study provides empirically-grounded guidelines for decision-making and resource optimization, contributing to improved hospital operational efficiency. This analysis can serve as a model for similar studies in other healthcare institutions, aimed at enhancing their efficiency and quality of services provided.